Incidence of postoperative respiratory adverse events and its predictors among pediatric surgical patients at Hawassa University Comprehensive Specialized Hospital: a prospective follow-up study - Hordofa, Tesfaye Asefa; Tuna, Adisu Negesa; Bussa, Mulualem Bunare; Waqayo, Kirubel Tinsae; Bariso, Wudinesh Tamiru; Ayano, Gudeta Teku; Daba, Dugo Angasa; Mengistu, Kurabachew; Adare, Oliyad Eshetu; Kebede, Mengistu Yinges; Ilala, Tajera Tageza (Frontiers in Anesthesiology, 2025)
BackgroundPostoperative respiratory adverse events are impairments in the normal functions of respiration resulting from the patient's condition, anesthesia, and surgery. They may be associated with postoperative complications such as cardiorespiratory arrest, extended hospital stays, and increased morbidity and mortality. Hence, we aimed to assess the incidence of postoperative respiratory adverse events and their predictors among pediatric surgical patients at Hawassa University Comprehensive Specialized Hospital (HUCSH) in 2024.MethodsA prospective follow-up study was conducted using simple random sampling of 205 pediatric patients (aged 0–15 years). Data were collected using a structured questionnaire and analyzed using SPSS, version 26. Categorical data were analyzed using the chi-squared test and continuous data were analyzed by independent sample t-test. Multivariable regression was conducted to identify the independent predictors of postoperative respiratory adverse events. Adjusted odds ratios (AORs) and 95% confidence intervals (CIs) were used to measure the strength of association and statistical significance at a p-value <0.05.ResultsThe incidence of postoperative respiratory adverse events was 35.6% among the 205 participants. Age younger than 1 month (AOR: 9.1, 95% CI: 1.3–12.5), age 1 month–2 years (AOR: 3.6, 95% CI: 5.8–16.1), upper respiratory tract infections (AOR: 3.2, 95% CI: 1.4–9.93), intraoperative opioid analgesics (AOR: 2.53, 95% CI: 1.2–5.97), use of a cuffed endotracheal tube (AOR: 3.97, 95% CI: 1.4–11.6), and spontaneous ventilation techniques (AOR: 8.53, 95% CI: 2.9–24.9) were independent predictors of postoperative respiratory adverse events.ConclusionThe incidence of postoperative respiratory adverse events was high. Age younger than 2 years, upper respiratory tract infections, intraoperative opioid use, use of cuffed endotracheal tubes, and spontaneous ventilation techniques were independent predictors of postoperative respiratory adverse events. Proper preoperative optimization, avoiding cuffed endotracheal tubes (for infants <2 years), implementing multimodal analgesia, and the use of controlled ventilation may reduce the incidence of postoperative respiratory adverse events.